2019
DOI: 10.1152/ajprenal.00184.2019
|View full text |Cite
|
Sign up to set email alerts
|

Renal iron accelerates the progression of diabetic nephropathy in the HFE gene knockout mouse model of iron overload

Abstract: Diabetic nephropathy (DN) is the most common cause of end-stage renal disease associated with high mortality worldwide. Increases in iron levels have been reported in diabetic rat kidneys as well as in human urine of patients with diabetes. In addition, a low-iron diet or iron chelators delay the progression of DN in patients with diabetes and in animal models of diabetes. Possible maladaptive mechanisms of organ damage by tissue iron accumulation have not been well studied. We recently reported that iron indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…Ferroptosis is a form of regulated cell death that is induced by iron overloading ( 1 ). Renal iron accumulation has been proposed to promote the progression of DN ( 33 , 34 ). However, Ferrostatin-1 can form a complex compounded with iron ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ferroptosis is a form of regulated cell death that is induced by iron overloading ( 1 ). Renal iron accumulation has been proposed to promote the progression of DN ( 33 , 34 ). However, Ferrostatin-1 can form a complex compounded with iron ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…Degradation of heme by the excessive HO-1 leads to iron overloading which causes oxidative stress and lipid peroxidation. Recent studies have documented the great effects of iron accumulation in kidneys on the progression of DN ( 33 , 34 ). These studies suggested that the process of ferroptosis might affect the development of DN, diabetic renal tubular injury in particular, through HIF-1α/HO-1 pathway.…”
Section: Introductionmentioning
confidence: 99%
“…In a diabetic circumstance, cytokines cause an increase in transferrin receptors on the cell surface, favoring tissue accumulation of transferrin and deposition of iron 32 . Iron nephrotoxicity is due to 1) the production of cell-damaging reactive radicals by Fenton reactions, and 2) ferroptosis, programmed cell death triggered by iron 33 , and 3) iron-induced RAS activation by upregulation of intra renal renin expression 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Through these mechanisms, iron overload aggravated the progression of DR in mice. Chaudhary et al 33 reported that renal iron accelerated the progression of diabetic nephropathy in association with renal–renin–angiotensin system activation. These results remain to be confirmed in future clinical research.…”
Section: Discussionmentioning
confidence: 99%